Development of a battery of computerized time- sharing tests - Šverko, Branimir; Jerneić, Željko (1995)
Time sharing is the term used to describe simultaneous performance of two or more tasks. Such performance is a typical of many complex, high-pressured jobs. Pilots, air-traffic controllers, or even car drivers, for example, are often pressured to divide their attention among several virtually concurrent tasks. Yet the assessment of their abilities in typical selection procedure is traditionally based on a serial approach, in which tests of an assessment battery are administered singly, one by one. For several years, in our laboratory we have explored the possibilities of a parallel approach, in which two assessment tasks are administered concurrently. Some data in favour of this approach will be presented, and an experimental battery of computerized time-sharing tests will be described.
ENG